Analysis of the Root Causes of an Undesirable Incident in a Hospital in Mashhad, 2013 - Zohourian, Parvin; Amini, Azam Sadat; Davooodi, Rozita; Shojaeian, Maryam (Bangladesh Journal of Medical Science, 2017)
Background and Objective: Medical errors are equivalent to costly failures. In other words, it is the behavior and/or decision which do not comply with healthcare standards. Thus, this study aimed to analyze the root causes of an undesirable incident which lead to the death of a 24-yearold intern who had been in contact with a patient with Crimean-Congo Hemorrhagic Fever (CCHF). She was referred to the infectious section with symptoms of a cold and fever which was accompanied by hemorrhage and respiratory distress. Unfortunately, she passed away four days later in one of the hospitals in Mashhad in 2013. Case Report: The current research is a descriptive study which was conducted through the qualitative method in 5 steps. The steps were as follows: defining the incident, data collection, outlining the identification of the issues, data analysis and identification of the root causes and working out solutions and implementation concerning the same incident in May 2013. Analysis of the root causes dated from May 2013 to June 2013. In the process, such tools as diagramming Cause and effect and storming thoughts were applied. Findings: A number of reasons were identified to have given rise to the incident. The lack of quarantine areas in the emergency section of the hospital, the negligence of the senior resident of the infectious diseases ward as to consider the need to isolate the patients, the negligence of the responsible intern as to take into account the similar cases which had been recorded in the morning report of the hospital on the same day, inadequate surgical consultations given by the senior resident according to the hospital policy and last but not least, inefficient education in universal precautions of the disease for the staff and students. Conclusions: The analysis of such fatal errors in the field of patient safety is of paramount importance. Thus, these techniques should be used in healthcare centers in order to evaluate critical situations systematically. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.580-587